Worlds, words, and spaces of resistance: Democracy and social media in consumer co-ops. (July 2020) - Barros, Marcos; Michaud, Valérie
This article explores how members of one of the largest Canadian consumer co-ops, reacting to what they saw as an assault on its democratic principles, use social media to try resisting the attempt from the board of directors to change its governance rules. Building on the Economies of Worth and Critical discourse analysis joint framework that considers power relations in the justification context, we unveil two essential moments. Initially, our analysis points to hegemonic justification struggles marked by the board and resisting consumer-members drawing on and reordering multiple worlds to debate the risk of democratic degeneration in consumer co-ops. Second, the critical insights suggest that the hegemonic control over the official deliberative arena pushed dissenting actors toward social media, an alternative space where they could deconstruct the co-ops-controlled discursive arena and create new conditions of possibility. Our article contributes to the literature on democratic degeneration in alternative organizations. More specifically, in the case of large consumer co-ops in which consumer-members have limited embodied presence, our results highlight how social media can offer a new space for debates, dissensus, and critical deconstruction. Our research also extends the post-structural criticism of the domination tendency of rational debate frameworks by showing that strategic displacement to new alternative spaces is essential to create new possibilities beyond those in central discursive arenas.